2018
DOI: 10.1121/1.5044423
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference for the ultrasonic characterization of rigid porous materials using reflected waves by the first interface

Abstract: The purpose of this paper is to present a method for the ultrasonic characterization of air-saturated porous media, by solving the inverse problem using only the reflected waves from the first interface to infer the porosity, the tortuosity, and the viscous and thermal characteristic lengths. The solution of the inverse problem relies on the use of different reflected pressure signals obtained under multiple obliquely incident waves, in the time domain. In this paper, the authors propose to solve the inverse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…In practice, it has been observed that foams with higher tortuosities might have lower characteristic viscous lengths, thus denoting a negative correlation between those two parameters, as opposed to the positive one observed during the inference. The same finding was reported in [28], where a correlation between φ and α ∞ was evidenced when the inference was performed with reflected signals.…”
Section: B Identification Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In practice, it has been observed that foams with higher tortuosities might have lower characteristic viscous lengths, thus denoting a negative correlation between those two parameters, as opposed to the positive one observed during the inference. The same finding was reported in [28], where a correlation between φ and α ∞ was evidenced when the inference was performed with reflected signals.…”
Section: B Identification Resultssupporting
confidence: 84%
“…We preferred to give what we thought was a reasonable value of Σ . Furthermore, we know [21,38,22,25,23] that the thermal characteristic length Λ is usually a factor 2 − 3 greater than Λ, and that its identification is problematic due to a low sensitivity [39,28]. As a result, Λ is set to 3Λ in the following, as was done in Refs.…”
Section: B Parameters Sensitivity To the Transmitted Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the relative error of Im (R M −R O ) ≈ 10%. The imaginary part of the reflection coefficient, and where it changes sign, can be key for characterising random microstructure [48]. The real part of the reflection coefficients is not shown, as the relative errors for the real part are even smaller.…”
Section: Comparing Reflection Coefficientsmentioning
confidence: 99%
“…The relationship between the acoustic impedances does not only have to do with the modification of the amplitude of the incident wave: it is also related to the fraction of the incident energy that will be reflected or transmitted. Most of the acoustic properties of materials can be studied by the application of new laboratory and numerical methods as ultrasonic characterization [4], inverse characterization with basis on the acoustic impedance measurement [5], or ensemble averaged scattering [6].…”
Section: How Does Sound Insulation Occur?mentioning
confidence: 99%